(untitled) (Journal of the College of Basic Education, 2026)
The research dealt with images of the Crusades presented by the French Orientalist René Grousset in his book (A Summary of the Crusades in the Islamic East and the Eastern Mediterranean Basin). It attempted to analyze the natural view of the Crusades, their causes and results from a Western perspective. Grousset is considered one of the most important French historians and the one most interested in the history of the East. He presented a comprehensive view of the Crusader-Islamic conflict in that era, and focused on several aspects, including the military, political and cultural aspects that accompanied those campaigns. The historian showed in his writings that he was not biased towards the West, but rather conveyed the picture in a balanced way and adopted the idea transparently, showing the progress and strength of the Arabs. He mentioned the Arab leader Saladin al-Ayyubi as a brave and noble leader who was distinguished by his chivalry and good qualities. He also criticized some of the actions committed by the Crusaders during their campaigns, especially when they entered Jerusalem and other cities.